Molecular breeding of pigs in the genome editing era - Jiahuan Chen; Jiaqi Wang; Haoran Zhao; Xiao Tan; Shihan Yan; Huanyu Zhang; Tiefeng Wang; Xiaochun Tang (Genetics Selection Evolution)
Abstract Background To address the increasing demand for high-quality pork protein, it is essential to implement strategies that enhance diets and produce pigs with excellent production traits. Selective breeding and crossbreeding are the primary methods used for genetic improvement in modern agriculture. However, these methods face challenges due to long breeding cycles and the necessity for beneficial genetic variation associated with high-quality traits within the population. This limitation restricts the transfer of desirable alleles across different genera and species. This article systematically reviews past and current research advancements in porcine molecular breeding. It discusses the screening of clustered regularly interspaced short palindromic repeats (CRISPR) to identify resistance loci in swine and the challenges and future applications of genetically modified pigs. Main body The emergence of transgenic and gene editing technologies has prompted researchers to apply these methods to pig breeding. These advancements allow for alterations in the pig genome through various techniques, ranging from random integration into the genome to site-specific insertion and from target gene knockout (KO) to precise base and prime editing. As a result, numerous desirable traits, such as disease resistance, high meat yield, improved feed efficiency, reduced fat deposition, and lower environmental waste, can be achieved easily and effectively by genetic modification. These traits can serve as valuable resources to enhance swine breeding programmes. Conclusion In the era of genome editing, molecular breeding of pigs is critical to the future of agriculture. Long-term and multidomain analyses of genetically modified pigs by researchers, related policy development by regulatory agencies, and public awareness and acceptance of their safety are the keys to realizing the transition of genetically modified products from the laboratory to the market.